Assessment of Gastric Emptying Times Between Pediatrics and Adults With Cyclic Vomiting Syndrome. Issue 9 (October 2020) - Kamal, Afrin; Sarvepalli, Shashank; Selvakumar, Praveen; Lopez, Rocio; Radhakrishnan, Kadakkal; Gabbard, Scott
Abstract : Background & Aims: Cyclic vomiting syndrome (CVS) is characterized by episodes of nausea and vomiting separated by symptom-free intervals. Rome IV guidelines have now distinguished CVS from other disorders such as cannabinoid hyperemesis. The pathogenesis of CVS, however, is poorly understood. Limited data exist on gastric emptying (GE) in patients with CVS. Therefore, the authors aim to measure the GE profile in pediatrics and adults with CVS. Materials and Methods: Patients with the diagnosis of CVS (per NASPGHAN and Rome IV) between December 1998 and March 2017 who underwent gastric emptying study (GES) and without documented cannabis use were included. Clinical features including demographics, medication use, and comorbidities were also recorded. Frequency of rapid, normal, and delayed emptying was reported, and multinomial univariate logistic regression was used to identify factors associated with each type of emptying. Key Results: Sixty-seven subjects were included (50.7% female individuals, pediatrics n=15, adults n=52). At 2-hour retention, 40% of pediatric patients met criteria for rapid, 33.3% for normal, and 26.7% for delayed GE. In adults, 50% met criteria for rapid, 46.2% for normal, and 3.8% for delayed GE. For every 5-year increase in age, odds of rapid emptying on GES increased. Conclusions: (1) GE is predominantly rapid at 2 hours in pediatrics and adults with CVS. (2) Rapid GE seems to increase with age. (3) Current guidelines do not recommend GE in the initial management, however, further studies may play a role to help differentiate CVS from other functional gastric disorders.